Design and Optimization of Psychological Emergency Response System for College Students Based on IoT and Computational Intelligence - Wang, Xiaoli (Mobile information systems, 2022)
Today, when university students are the future subjects of society, psychological crises are constantly emerging. At the same time, considering the rapid socioeconomic development, competition among the best talents, cultural diversity, and the growth of temptations and events in public health, all of these put growing students through the wringer. However, when traditional sentiment data are analyzed through manual selection, it usually has some drawbacks such as small sample size, poor real-time status, high transaction costs, and high human errors. We need to use modern technology, applied technology, and computer intelligence to collect psychological data from all respondents, which is ultimately measured by sentiment data. Use the results of emotional data analysis to deal with emergencies in a timely manner. The system designed in this paper has unprecedented advantages in terms of automation, timeliness, and accuracy compared to previous participatory psychotherapy methods.